Social media's effect on purchase intentions - Sitto, Morwesi Karabo (My University, 2015)
Social media has grown significantly over the last decade and so has its influence on relationships between customers and marketing organisations. The question of the potential return for organisations from investing resources and time in using social media as a relationship marketing tool is one marketing managers struggle to answer adequately. Through building scenarios, both the perceived risk of investing in social media relationship marketing and the customers’ ability to benefit from such relationship building efforts were examined. Four online questionnaires were sent to different target groups to find answers about social media’s effect on customer purchase intentions. This included a close study of the relationship between gratitude and its effect on purchase intentions. The key finding from this research is that higher customer gratitude through social media interactions results in higher customer purchase intentions. The investment in social media as a relationship marketing tool is worthwhile for organisations to undertake, but only in the context of overall relationship marketing efforts to drive up company performance outcomes.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014